A new species of Canon Solovyev, 2014 (Lepidoptera: Limacodidae) from Thailand - Pellinen, Markku J.; Solovyev, Alexey V. (Zootaxa, 2015)
Canon Solovyev is a small genus belonging to the Parasa-complex of Limacacodidae. It is distributed from northern India to the Malayan Peninsula. The genus previously included two species: C. punica (Herrich-Schäffer) from the Indian region and C. eos Solovyev from Nepal. Canon punica is recorded from China (Yunnan), northern Thailand and Malaysia, but specimens from northern Thailand and probably those from China (Yunnan) represent a new species that is described herein: C. sripanae Pellinen and Solovyev, new species. Externally, C. sripanae is similar to other Canon species, but it differs from punica and eos in hindwing color and male genitalia. The moths studied were collected at UV and mixed lights. Genitalia of the male holotype and a male and female paratypes are figured. Nomenclature of this study is based on Solovyev (2014).